Implementation of Adaptive Core Value: Review of Bali Province CPNS BKPSDM Learning Process in 2022 - Ni Made Suciani (Monas: Jurnal Inovasi Aparatur, 2024)
This research aims to describe how the Adaptive Core Value learning process can explain the Adaptive performance profile of Basic Training participants for Agenda II Civil Servant Candidates using the classical training model. The learning process for participants aims to understand the concept of Adaptiveness and actualize adaptive values in carrying out their job duties. From the concept findings and implementation, the learning process achieved will be put into practice and described; in addition to that, an instrument will be developed to see the participant's adaptive performance profile. This research used descriptive quantitative and qualitative methods with purposive random sampling involving participants from Batch I and XVII of 2022 at the Personnel and Human Resources Development Agency of Bali Province. The results of the book review found that the Adaptive Core Value concept leads to adaptive performance, which contains the dimensions: 1) handling emergency/crisis situations; 2) managing work stress; 3) solving problems creatively; 4) facing an uncertain work situation; 5) training and learning efforts; 6) interpersonal adaptation; 7) work culture adaptation; and 8) physical adaptation. The findings in this research show that all dimensions of Adaptive performance have emerged in the learning process in Adaptive training courses. In line with this, the participant's Adaptive performance profile is high. Thus, there is a match between the achievements in the learning process and the participants' adaptive performance profiles. Learning is not limited to concepts and theories but how they can actualize these Adaptive values in the form of Adaptive performance in the learning process. It is hoped that the results of this research can be a reference in learning Agenda II Core Values of ASN with AKHLAK on Adaptive values and can develop other Core Values of ASN with AKHLAK.